DETERMINATION OF MAJOR AND TRACE ELEMENTS IN ARTEMISIA ELEGANFISSIMA ANDRHAZYA STRICTA AND THEIR RELATIVE MEDICINAL USES - Kanee, FA; Qadiruddin, M; Kalhoro, M A; Khaula, S; Badar, Y (Biological Sciences - PJSIR, 2001)
Artemisia elegantissima and Rhazya stricta have been explored to determine major and trace elements and their possible role in human health. Thirteen trace elements have been studied in both the plants which were found to be rich in Cu, Co, Fe, Mg, Mn and Zn. These trace elements are reputed being main constituents for human health and for curing some diseases. They are also found to be rich in nutrient elements which are best source for fodder.